The fight of our lives : my time with Zelenskyy, Ukraine's battle for democracy, and what it means for the world - Mendelʹ, I͡Ulii͡a (One Signal Publishers/Atria Books, 2022)
"In this frank and moving inside account, Zelenskyy's former press secretary tells the story of his improbable rise from popular comedian to the president of Ukraine. Mendel had a front row seat to many of the key events preceding the 2022 Russian invasion. From attending meetings between Zelenskyy and Putin and other European leaders, visiting the front lines in Donbas, to fielding press inquiries after the infamous phone calls between Donald Trump and Zelenskyy that led to Trump's first impeachment. Mendel saw firsthand Zelenskyy's efforts to transform his country from a poor, backward Soviet state into a vibrant, prosperous European democracy. Mendel sheds light on the massive economic problems facing Ukraine and the entrenched corrupt oligarchs in league with Russia. She witnessed the Kremlin's repeated attacks to discredit Zelenskyy through disinformation and an army of bots and trolls. Woven into her account are details about her own life as a member of Zelenskyy's new Ukraine. Written with the sound of Russian bombs and exploding shells in the background, Mendel details life lived under Russian siege in 2022. She says goodbye to her fiancé who joins the front lines, like so many other Ukrainian men. Throughout this story of Zelenskyy, Ukraine, and its extraordinary people, Iuliia Mendel reminds us of the paramount importance of truth and human values, especially in these darkest of times"--